Association Between Alu Insertion/Deletion Polymorphism in Intron 8 of Human Tissue Plasminogen Activator Gene (PLAT) and Risk of Age-Related Macular Degeneration: PLAT and AMD - Ghorbani, Saghar; Saadat, Mostafa (Scripta Medica, 2023)
Background/Aim: Age-related macular degeneration (AMD) is major reason of blindness in human. Plasminogen is converted to plasmin by tissue plasminogen activator protein (PLAT, formerly known as TPA). A polymorphism in intron 8 of PLAT gene has been reported, either with (insertion) or without (deletion) a 311 bp Alu sequence. This polymorphism is associated with plasma levels of glycoprotein t-PA. t-PA is expressed in the retina and is involved in the development of the eye. It can be hypothesised that the PLAT polymorphism may be correlated with AMD. Therefore, the current study was conducted. Methods: A total of 121 AMD patients and 108 healthy subjects were included in the study. Genotyping was performed by PCR. The strength of the association between AMD and polymorphism was expressed by estimating the odds ratio (OR). Results: There was a significant relationship between the Del/Del genotype and susceptibility to AMD (OR = 2.25, 95 % CI = 1.07-4.69, p = 0.031). After adjusting for various factors such as age, smoking habit and workplace, a similar relationship was obtained (OR = 2.51, 95 % CI = 1.01-6.23, p = 0.049). Conclusions: The homozygosity of the Del allele was found to increase the susceptibility to AMD. This polymorphism may contribute to the risk of AMD in population.